Healthcare resource utilization and costs in patients with HIV-1 who switched first-line antiretroviral therapy. (2nd November 2019) - Mao, Jianbin; Johnson, Michael P.; McPheeters, Jeffrey T.; Prajapati, Girish; Beyer, Andrew P.
Abstract: Objectives: This study compared healthcare utilization and costs associated with switching the first-line protease inhibitor (PI) or non-nucleoside reverse transcriptase inhibitor (NNRTI) based antiretroviral (ARV) regimen due to reasons other than virologic failure among patients with HIV-1. Methods: This was a retrospective analysis of commercial and Medicare Advantage with Part D enrollees in two US administrative claims databases. The study population comprised adults with HIV-1 infection initiating antiretroviral therapy (ART) on PI- or NNRTI-containing regimens from 1 January 2006 to 31 December 2015. Patients with a subsequent change in anchor agent were assigned to the switch cohort; the non-switch cohort was constructed using propensity score matching of three non-switching patients for each patient in the switch cohort. Patient characteristics and per patient per month healthcare resource utilization and costs were compared between the cohorts during the pre-switch, switch (15 days before and after switching) and post-switch periods. Costs during the switch period were also estimated with a multivariable-adjusted model. Results: The matched study population consisted of 1204 patients who switched their first-line PI- or NNRTI-based regimen and 3612 patients who did not. Compared with the non-switch cohort, patients who switched had higher healthcare resource utilization during the pre-switch, switch and post-switch periods. Mean unadjusted non-ART costs in the switch cohort were nearly double ($2944 versus $1530, p <  .001), more than double ($2562 versus $1215, p <  .001) and 1.5 times higher ($1473 versus $968, p <  .001) than costs in the non-switch cohort in the pre-switch, switch and post-switch periods, respectively. Conclusions: Patients with HIV-1 who initiated PI- or NNRTI-based regimens and switched ARTs for reasons other than virologic failure used more healthcare resources and incurred greater costs relative to patients in the non-switch cohort. This study highlights the importance of initiating patients on appropriate first-line ART to avoid the need to switch due to reasons other than virologic failure.